2012
DOI: 10.1186/1472-6882-12-176
|View full text |Cite
|
Sign up to set email alerts
|

Potent α-glucosidase and α-amylase inhibitory activities of standardized 50% ethanolic extracts and sinensetin from Orthosiphon stamineus Benth as anti-diabetic mechanism

Abstract: BackgroundIn the present study, we tested a 50% ethanolic extract of Orthosiphon stamineus plants and its isolated bioactive compound with respect to their α-glucosidase and α-amylase inhibitory activities.MethodsBioactive flavonoid sinensetin was isolated from 50% ethanolic extract of Orthosiphon stamineus. The structure of this pure compound was determined on the NMR data and the α-glucosidase and α-amylase inhibitory activities of isolated sinensetin and 50% ethanolic extract of Orthosiphon stamineus were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(127 citation statements)
references
References 26 publications
5
110
0
8
Order By: Relevance
“…Indonesia menempati posisi ketujuh negara dengan penderita diabetes terbanyak di dunia (IDF, 2013). Kumis kucing merupakan tanaman obat tradisional Indonesia yang digunakan untuk mengobati diabetes dengan cara menghambat aktivitas enzim pencernaan salah satunya enzim α-glukosidase (Mohamed et al, 2011;Mohamed et al, 2012). Selain anti hiperglikemik, tanaman kumis kucing kaya akan senyawa antioksidan (Akowuah et al, 2005) sehingga kumis kucing berpotensi pula untuk menurunkan risiko komplikasi diabetes akibat stres oksidatif (Baynes dan Thorpe, 1999).…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Indonesia menempati posisi ketujuh negara dengan penderita diabetes terbanyak di dunia (IDF, 2013). Kumis kucing merupakan tanaman obat tradisional Indonesia yang digunakan untuk mengobati diabetes dengan cara menghambat aktivitas enzim pencernaan salah satunya enzim α-glukosidase (Mohamed et al, 2011;Mohamed et al, 2012). Selain anti hiperglikemik, tanaman kumis kucing kaya akan senyawa antioksidan (Akowuah et al, 2005) sehingga kumis kucing berpotensi pula untuk menurunkan risiko komplikasi diabetes akibat stres oksidatif (Baynes dan Thorpe, 1999).…”
Section: Pendahuluanunclassified
“…Ekstrak etanol daun kumis kucing dilaporkan memiliki aktivitas penghambatan terhadap enzim α -glukosidase dengan IC 50 sebesar 4,63 mg/mL (Mohamed et al, 2012) lebih besar dibandingkan dengan nilai IC 50 yang diperoleh dari hasil penelitian yaitu sebesar sebesar 465,83 µg/mL. Perbedaan asal geografis tempat tumbuh, jenis pelarut dan bagian tanaman yang yang digunakan mem-pengaruhi kandungan bioaktif sehingga dapat menyebabkan perbedaan aktifitas biologis dari tanaman kumis kucing (Rafi et al, 2015;Akowuah et al, 2005).…”
Section: Hasil Dan Pembahasan Aktivitas Penghambatan α-Glukosidase Ekunclassified
See 2 more Smart Citations
“…The O. stamineus extract used in this study was more in a crude form, which may explain its low antibacterial activity. Previous studies which reported the protective effects of O. stamineus employed methanolic (Chun-Hoong et al, 2010;Malahubban et al, 2013) and ethanolic extracts (Alshawsh et al, 2012;Mohamed et al, 2012).…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%